Bong Joon Ho - Jeon, Joseph Jonghyun 1971- (Contemporary film directors, 2024)
"Successful cult films like The Host and Snowpiercer proved to be harbingers for Bong Joon Ho's enormous breakthrough success with Parasite. Joseph Jonghyun Jeon provides a consideration of the director's entire career and the themes, ambitions, techniques, and preoccupations that infuse his works. As Jeon shows, Bong's sense of spatial and temporal dislocations creates a hall of mirrors that challenges us to answer the parallel questions Where are we? and When are we? Jeon also traces Bong's oeuvre from its early focus on Korea's US-fueled modernization to examining the entanglements of globalization in Mother and his subsequent films. A complete filmography and in-depth interview with the director round out the book. Insightful and engaging, Bong Joon Ho offers an up-to-date analysis of the genre-bending international director"--